Emerging adults’ identity exploration: Illustrations from inside the ‘camp bubble. - Johnson, Sara K. ; Goldman, J. A. ; Garey, A. I.; Britner, P. A.; Weaver, S. E. (Tufts University. Tisch Library., 2016)
The study investigates the experiences of emerging adults who had worked as counselors at overnight summer camps; identity-related issues emerge as most salient in the analysis of in-depth interviews conducted with 12 women and 8 men from 8 camps. Their descriptions portray the identity exploration that took place within the camp context, through opportunities to try out roles and responsibilities ranging from the adult-like role model to the more child-like entertainer, and many counselors specifically remark on the role of camp experiences in their identity development. The role of camps as one type of facilitative venue for emerging adults’ identity exploration is discussed.